D’un genre cinématographique à l’autre : trois adaptations en westerns dans le cinéma américain d’après 1945 - Mathieu Lacoue-Labarthe (Itinéraires)
Between 1949 and 1954, three movies directed by Raoul Walsh and Joseph Mankiewicz are adapted into westerns by Walsh and Edward Dmytryk. In some respects, these movies are simply transposed from one genre to the other, with great fidelity. Some other aspects are altered to fit the Western genre’s codes and conventions (importance of action, praise of the hero and family). In some cases, there is no possible equivalent between the two genres: House of Strangers’ social criticism gives way to the denunciation of racism in Broken Lance. On the contrary, the influence of psychoanalysis in both House of Strangers and Colorado Territory, which have nothing else in common, is due to the fact that these works are produced the same year. Colorado Territory is ultimately the remake which draws the most inspiration from its model, High Sierra, and its adoption of some of the film noir characteristics makes it a precursor to the Revisionist Western.